2013
DOI: 10.33084/anterior.v13i1.295
|View full text |Cite
|
Sign up to set email alerts
|

Pelaksanaan Pengukuran Ranah Kognitif, Afektif, Dan Psikomotor Pada Mata Pelajaran Ips Kelas Iii Sd Muhammadiyah Palangkaraya

Abstract: This procedure is also to eliminate subjectivity in research results. The sample in this study were all third grade students of Muhammadiyah Elementary School Palangkaraya, and because the population was less than 100 people, all third grade students of Muhammadiyah Elementary School became the research sample. The variables in this study are cognitive, affective and psychomotor domains. Data collection methods or techniques are using the question method or in the form of tests and observations. While the inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
19

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 0 publications
0
14
0
19
Order By: Relevance
“…The benefit of measuring affective domains is to improve the achievement of instructional goals by students in the affective domain, especially at the level of acceptance, participation, assessment, organization and internalization. In addition, it can improve students' attitudes, interests, self-concepts, values and morals (Nurbudiyani, 2013). Psychomotor domains are basically learning standards according to industry needs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of measuring affective domains is to improve the achievement of instructional goals by students in the affective domain, especially at the level of acceptance, participation, assessment, organization and internalization. In addition, it can improve students' attitudes, interests, self-concepts, values and morals (Nurbudiyani, 2013). Psychomotor domains are basically learning standards according to industry needs.…”
Section: Introductionmentioning
confidence: 99%
“…Psychomotor domains are basically learning standards according to industry needs. The benefits of the psychomotor domain are in addition to improving the achievement of instructional objectives by students in the psychomotor realm, especially at the level of imitation, manipulation, precision, articulation, and naturalization, it can also increase students' reflex ability, basic movements, perceptual skills, physical skills, skilled movement, and non-discussive communication (Nurbudiyani, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini dikarenakan IPS berhubungan dengan kehidupan sosial siswa sehingga dengan mengaitkanya dapat menimbulkan proses internalisasi siswa pada diri siswa sekolah dasar. IPS harus mampu menyelaraskan aspek lainya dalam belajar seperti aspek keterampilan , sikap dan pengetahuan (Nurbudiyani, 2013 PBL merupakan pembelajaran kontekstual yang menjadikan permasalahan nyata menjadi sebuah pembelajaran (Kenedi, 2017). PBL menyajikan masalah yang telah terjadi kemudian siswa diminta untuk menemukan infromasi melalui sumber belajar lainya dengan melibatkan kemampuan berpikir dan keterampilan lainya baik secara individu maupun kolaborasi (Kiswanto, 2017).…”
Section: Pendahuluanunclassified
“…The determinant of the success of the achievement of a social studies learning is the learning outcome. "In general, learning outcomes can be grouped into three aspects, namely: the cognitive domain, the affective domain, and the psychomotor domain, and explicitly these three aspects cannot be separated from one another" [2]. From this opinion, it can be concluded that social studies learning outcomes have 3 defining aspects, namely aspects in the cognitive realm obtained through learning activities that have been carried out by students, then aspects in the affective domain, namely through changes in attitudes experienced and finally in the psychomotor realm there is a change in behavior.…”
Section: Introductionmentioning
confidence: 99%